Evaluasi Tingkat Keberhasilan E-Learning Smart Campus Menggunakan Metode HOT FIT - Muhammad Munawir Arpan; Idria Maita; Fitriani Muttakin; Febi Nur Salisah (Journal of Information System Research (JOSH), 2023)
E-learning Smart Campus is a website that is used as an electronic learning system. Smart Campus e-learning began to be implemented at STIFAR Riau in 2018. In this study there were several problems during its use not all lecturers used it, frequent errors occurred, lack of training for system users, difficulty uploading assignments to the system. The purpose of this research is to determine the success rate of implementing Smart Campus e-learning and to provide suggestions for improvements to become a better system for the future. The method used to measure the success rate of Smart Campus e-learning is the HOT Fit method. Respondents in this study were students and lecturers of STIFAR Riau with a total sample of 313 respondents. For data processing using the SEM-PLS technique with SmartPLS software. The results of testing the successful implementation of STIFAR Riau E-learning from the 12 hypotheses used obtained the highest value, namely the variable User Satisfaction on Net Benefit with a T-Stasistic value of 7,494. This means that the better the User Satisfaction, the higher the System User in using the Smart Campus Riau E-learning System.